2020
DOI: 10.1186/s12910-020-00516-z
|View full text |Cite
|
Sign up to set email alerts
|

“You would not be in a hurry to go back home”: patients’ willingness to participate in HIV/AIDS clinical trials at a clinical and research facility in Kampala, Uganda

Abstract: Background Few studies have examined factors associated with willingness of people living with HIV (PLHIV) to participate in HIV treatment clinical trials in Sub-Saharan Africa. We assessed the factors associated with participation of PLHIV in HIV treatment clinical trials research at a large urban clinical and research facility in Uganda. Methods A mixed methods study was conducted at the Infectious Diseases Institute (IDI), adult HIV clinic between July 2016 and Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 40 publications
(32 reference statements)
2
6
0
Order By: Relevance
“…16 The survey in Uganda also found that side effects like treatment failure and uncertainty about privacy of their data were barriers to participation. 19 This is consistent with our findings that 94.8% of the 344 people who were reluctant to participate in cure research had safety concerns.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…16 The survey in Uganda also found that side effects like treatment failure and uncertainty about privacy of their data were barriers to participation. 19 This is consistent with our findings that 94.8% of the 344 people who were reluctant to participate in cure research had safety concerns.…”
Section: Discussionsupporting
confidence: 91%
“…A previous study demonstrated that a satisfactory compensation package significantly influenced participation in HIV treatment clinical trials. 19 The compensation offered during trials may attract more individuals engaging in physical labor than company employees who have a stable income, regular working hours, insurance coverage and likely a more conservative attitude toward risks. Awareness of functional cure may increase the willingness to participate in a trial that offers a possible therapeutic prospect.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations